Comportamento alimentar de alevinos de tilápia do Nilo (Oreochromis niloticus) e de dourado (Salminus brasiliensis) submetidos a diferentes frequências de arraçoamento - Pires, Grace Kelly Goudinho (2022)
The present study aimed to evaluate the feeding behavior of Nile tilapia (Oreochromis niloticus) and dorado (Salminus brasiliensis) fingerlings submitted to different feeding frequencies. For the trial twelve fish were observed for a period of twenty-two days. Six Nile tilapia fingerlings with mean weight 8.13 ± 1.64 g, standard length 5.86 ± 0.59 cm and total length 7.4 ± 0.68 cm and six gilthead sea bream fingerlings with mean weight 4.85 ± 1.01 g, standard length 6.6 ± 0.67 cm and total length 7.6 ± 0.68 cm were tested. The fish were distributed in an entirely randomized design in 12 aquaria, undergoing a three-minute filming trial. The fish were fed a commercial diet (32% BW), with a pellet diameter of 2.00 mm. The treatments consisted of three feeding frequencies: twice daily at 8am and 4pm (T1); four times daily at 8am, 11am, 2pm, and 5pm (T2) (control); and six times daily at 8am, 10am, 12pm, 2pm, 4pm, and 6pm (T3). To determine feeding behavior, the time to capture the first pellet, the total time to capture the pellets, the number of pellet rejections after capture, the number of approaches without capturing the pellet, the number of pellets consumed, attractiveness and palatability index, and attractiveness index were observed. The data were subjected to two-factor ANOVA parametric analysis of variance. All food frequencies analyzed can be used without altering the attractiveness and palatability index of the species. For the attractiveness index, T1 is recommended for gilthead sea bream, and T2 control is recommended for tilapia. There was no interaction and no significant difference in feeding behavior between Nile tilapia, sea bream and feeding frequency.